NEW PEDAGOGICAL TECHNOLOGIES AS A FACTOR OF INCREASING THE QUALITY OF EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article presents ideas and recommendations for the learning process and the use of educational technologies. The opinions on the importance of modern approaches to differentiated education are highlighted.